Praktik Binary Option Bertopeng Investasi Dari Perpsektif OJK - Ramadhani, Elsa; Karni, Nur Aisyah; Permata, Nella (Asosiasi Dosen Akuntansi Indonesia, 2023)
In Indonesia, binary options are still a relatively new financial product. New users of the binary options platform still do not realize that high risk is always correlated with predicted price fluctuations of the financial instruments used as assets. This study aims to try to investigate whether there are unlawful binary options trading activities in Indonesia, and examine whether there are causes of unethical actions used by binary options operators which result in losses for option holders. This study uses descriptive qualitative research using the literature review method by comparing, collecting, and analyzing previous research by leading to the existence of regulations. The findings of this study show that binary options are not a tool for trading or investing. The results of this study are that the Financial Services Authority (OJK) provides protection in the form of outreach and public education about the characteristics of fundraising efforts and oversight of illegal investments. Share information with regulators and law enforcement in places of oppression. In addition, under the coordination structure of the Investment Alert Task Force, better known as the Task Force for handling alleged unlawful acts in the field of fundraising and investment management, various agencies can work together to speed up the handling process.